INFLUENCE OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS ON MOVEMENT-RESEARCH BEHAVIOR OF ANIMALS UNDER EXPERIMENTAL SECONDARY OSTEOARTHRITIS - Nosivets, D.S.; Shevchenko, T.M.; Govorukha, O.Yu. (World of Medicine and Biology, 2022)
The study was performed on 160 white nonlinear rats, which reproduced experimental osteoarthritis by intra-articular injection of 0.1 ml monoiodoacetic acid solution and reproduced experimental hypothyroidism by enteral administration of 0.02 % carbimazole solution. Changes in motor-research behavior of animals are studied in the test “open field”. The detected changes on the 42nd day of the experiment in all groups of animals indicate the suppression of motor and research activity against the background of increasing pathological changes under the influence of experimental models. Decreased motor activity indicates the development of pain in the knee joints of animals, which limits their movement. It was found that the appointment of L-thyroxine at a dose of 1.5 μg/kg highlights the trend of recovery of spontaneous behavioral activity, and the use of paracetamol at a dose of 150 mg/kg and L-thyroxine contributes to greater inhibition of motor and research activity of rats.